1975
DOI: 10.1136/oem.32.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo effect of inorganic lead and cadmium on glutathione reductase system and delta-aminolevulinate dehydratase in human erythrocytes.

Abstract: The activity of delta-aminolevulinate dehydratase (ALAD) of erythrocytes, the lead (Pb-B) and cadmium (Cd-B) concentration in whole blood, the content of reduced glutathion (GSH) in erythrocytes, and the regeneration rate of GSH by intact erythrocytes were measured during an epidemiological survey of 84 men employed in a Belgian cadmium and lead producing plant. A control group of 26 persons (students and laboratory staff) was also examined. The logarithm of the ALAD activity is highly inversely correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…Regarding the decrease observed in GSH levels in lead-exposed subjects (Roels et al 1975 ;Mohammad et al 2008 ), experimental studies have also found a significant decline in GSH levels due to lead exposure (Wang et al 2009 ;Martinez-Haro et al 2011 ). In contrast, in the study by Conterato et al ( 2013 ), GSH levels were elevated in lead-exposed workers with lower BLLs (5.4 ± 0.4 μg/dL) but not in workers with higher BLLs (49.8 ± 4.0 μg/dL).…”
Section: Types and Utility Of Biomarkerscontrasting
confidence: 51%
See 1 more Smart Citation
“…Regarding the decrease observed in GSH levels in lead-exposed subjects (Roels et al 1975 ;Mohammad et al 2008 ), experimental studies have also found a significant decline in GSH levels due to lead exposure (Wang et al 2009 ;Martinez-Haro et al 2011 ). In contrast, in the study by Conterato et al ( 2013 ), GSH levels were elevated in lead-exposed workers with lower BLLs (5.4 ± 0.4 μg/dL) but not in workers with higher BLLs (49.8 ± 4.0 μg/dL).…”
Section: Types and Utility Of Biomarkerscontrasting
confidence: 51%
“…In 3 studies, GSH levels decreased in the exposed group (Mohammad et al 2008 ;Feksa et al 2012 ;Kasperczyk et al 2013b ) and were negatively correlated with BLLs in the Lead Exposure and Oxidative Stress: A Systematic Review 226 other study ( r = −0.423; p < 0.001) (Roels et al 1975 ). However, GSH levels increased in the exposed group and were also negatively correlated with ALAD levels in another study (Gurer-Orhan et al 2004 ;Conterato et al 2013 ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 92%
“…Despaux et al (4) think that modifications of the activity of ALA-D are explained by an action of the metals at different levels: thiol groups, allosteric sites, zinc site, and an indirect mechanism at the level of reduced glutathione, indispensable for ALA-D activity in vivo (9).…”
mentioning
confidence: 99%
“…other study ( r = −0.423; p < 0.001) (Roels et al 1975 ). However, GSH levels increased in the exposed group and were also negatively correlated with ALAD levels in another study (Gurer-Orhan et al 2004 ;Conterato et al 2013 ).…”
Section: Tablementioning
confidence: 70%
“…Regarding the decrease observed in GSH levels in lead-exposed subjects (Roels et al 1975 ;Mohammad et al 2008 ), experimental studies have also found a significant decline in GSH levels due to lead exposure Martinez-Haro et al 2011 ). In contrast, in the study by Conterato et al ( 2013 ), GSH levels were elevated in lead-exposed workers with lower BLLs (5.4 ± 0.4 μg/dL) but not in workers with higher BLLs (49.8 ± 4.0 μg/dL).…”
Section: Types and Utility Of Biomarkersmentioning
confidence: 96%